Current Prospects of Korean Reunification against the Background of the Interstate Relations - Stankiewicz, Wojciech (International Studies. Interdisciplinary Political and Cultural Journal, 2012)
Forecasts predicting the reunification of the Korean Peninsula were common throughout the 1990s. Since then, enthusiasm for such predictions has dampened, and though the fundamental assumption of reunification remains, predictions of when and how this will happen have been more restrained. Reunification leaves two unresolved yet interdependent issues: reunification itself, which is the urgent challenge; and the strategic issues that emerge from reunification, which have the potential to fundamentally transform strategic relations in the region of Northeast Asia. Within this context, this paper examines the prospects of Korean reunification against the background of the interstate relations. Initially, it will establish the framework from which such scenarios will emerge: the historical background of the division, the extreme differences between the two states, the role played by the North Korean nuclear threats and the impact of the September 11, 2001 on the interstate relations, and finally general situation and relations in the East Asian region. Then, three possible scenarios of the unification will be developed: through peaceful integration, through the fall of North Korea or through a war. Summing up, even the death of Kim Jong Il will not bring change in the domestic and foreign policy of North Korea which is going to continue an aggressive approach toward the South. In the short-term reunification is definitely not in the interest of the current ROK administration, and the South has no intention of encouraging it. None of the considered scenarios envisions early reunification, and it seems that for the future, the status quo on the Korean Peninsula will remain.